2011
DOI: 10.1016/j.diabres.2011.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Lower postprandial glucose responses at baseline and after 4 weeks use of a diabetes-specific formula in diabetes type 2 patients

Abstract: Superior PPG control by DSF was maintained after 4 weeks use, showing that this formula has added value with respect to PPG control for type 2 diabetes patients compared to a standard, fiber-containing formula. The observed effects on body weight, fasting glucose and HOMA(IR) may further support the use of a DSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 37 publications
3
25
1
1
Order By: Relevance
“…Diabetic patients are at risk of both malnutrition [ 11 ] and hospital readmissions [ 20 ], often requiring nutritional support [ 10 ]. Enteral HDSF have been specially developed for the treatment of malnourished diabetic patients, as well as for maintaining glycemic control [ 10 , 11 , 21 , 22 ] which, if not managed, can have profound consequences on clinical outcomes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic patients are at risk of both malnutrition [ 11 ] and hospital readmissions [ 20 ], often requiring nutritional support [ 10 ]. Enteral HDSF have been specially developed for the treatment of malnourished diabetic patients, as well as for maintaining glycemic control [ 10 , 11 , 21 , 22 ] which, if not managed, can have profound consequences on clinical outcomes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review of Elia et al [ 11 ] showed that DSFs improved glycemic control, compared to standard formulas. Lansink et al [ 21 ] published a study with T2DM patients receiving either specific or standard formula, finding that the HDSF did not affect fasting glucose levels and contributed to improving glycemic control. Finally, the systematic review published by Ojo et al [ 10 ] concluded that HDSF was more effective controlling glucose profiles, including postprandial glucose, HbA1c and insulinemic response.…”
Section: Discussionmentioning
confidence: 99%
“…Those participants in the highest quartile of meal replacement usage were approximately 4 times more likely to reach the 7% and 10% weight loss goal than participants in the lowest quartile (156). Meal replacements with differing macronutrient compositions designed for people with diabetes have shown no clear advantage, although studies remain lacking (157,158).…”
Section: Meal Replacementsmentioning
confidence: 99%
“…In a study involving insulin-treated patients with T2D who received enteral nutrition, the use of a low-carbohydrate, high monounsaturated fatty acid formula improved glycemic control compared with a standard enteral nutrition formula [38]. A more recent study showed that postprandial glucose responses were lower and were maintained during a 4-week trial of DSF in patients with T2D [39•]. Additionally, a systematic review showed that short-term and long-term use of DSF as oral supplementation and enteral nutrition support are associated with improved glycemic control compared with standard formulas [40].…”
Section: Transcultural Factors For Asiamentioning
confidence: 99%